13Check_RNA: A tool to evaluate 13 C chemical shift assignments of RNA - Icazatti Zuñiga, Alejandro Ariel (2018)
Motivation: Chemical shifts (CS) are an important source of structural information of macromolecules such as RNA. In addition to the scarce availability of CS for RNA, the observed values are prone to errors due to a wrong re-calibration or miss assignments. Different groups have dedicated their efforts to correct CS systematic errors on RNA. Despite this, there are not automated and freely available algorithms for evaluating the referencing of RNA 13 C CS before their deposition to the BMRB or re-reference already deposited CS with systematic errors. Results: Based on an existent method we have implemented an open source python module to correct 13 C CS (from here on 13 C exp ) systematic errors of RNAs and then return the results in 3 formats including the nmrstar one.